Significance of Cancer Stem Cells in Anti-Cancer Therapies - Botelho, Mónica (2017)
Stem cells are the focus of cutting edge research interest because of their competence both to self-renew and proliferate, and to differentiate into a variety of tissues, offering enticing prospects of growing replacement organs in vitro, among other possible therapeutic implications. It is conceivable that cancer stem cells share a number of biological hallmarks that are different from their normal-tissue counterparts and that these might be taken advantage of for therapeutic benefits. In this review we discuss the significance of cancer stem cells in diagnosis and prognosis of cancer as well as in the development of new strategies for anti-cancer drug design.